THE EFFECT PENGARUH RENDAMAN AIR HANGAT PADA KAKI TERHADAP TINGKAT INSOMNIA PADA LANSIA DI PUSKESMAS DESA TERJUN : PENGARUH RENDAMAN AIR HANGAT PADA KAKI TERHADAP TINGKAT INSOMNIA PADA LANSIA - Syafitri, Endryani; Mardha, Muthia Sari; Marsaulina, Ivansri; Syahrani, Rini (Fakultas Ilmu Kesehatan, 2025)
Insomnia in the elderly generally occurs frequently related to physical and psychological conditions, where the body's condition begins to be vulnerable and mentally begins to become unstable. Many elderly people are not ready to deal with these changes, so that it becomes a burden on their minds and is related to sleep quality, resulting in insomnia. To treat primary insomnia, you can use non-formological therapies such as warm baths. This study aims to determine the effect of warm water immersion on the elderly's feet on the level of insomnia in the elderly at the Waterfall Village Health Center before and after giving warm water immersion in the experimental and control groups.This study used a quasi-experimental method with a nonquivalent control group. The sample consisted of 20 respondents who were divided into 2 groups, namely 10 experimental groups and 10 control groups. With univariate and bivariate data analysis using a parametric test, namely the paired sample T-test. The results showed that the average level of insomnia after being given a warm water immersion in the experimental group was 1.60 while in the control group (posttest) it was 2.00 with a mean difference of -1.400 and a p-value of 0.050 (=0.05). The conclusion of this study showed that there were differences in the effect of warm water immersion on the level of insomnia in the experimental and control groups. It is recommended for the elderly to do it 2 times a week as a way to reduce insomnia. Keywords: Warm Water Soak, Insomnia Level